Ecology of waders in the Jeram and Remis mudflats, Selangor Darul Ehsan / Nor Atiqah Norazlimi - Nor Atiqah, Norazlimi (2016)
The objectives of this project were to study the distribution and abundance of waders shorebird and water bird species, to study the factors (i.e. tide, time of the day and disturbance) affecting the distribution and behaviour of waders shorebirds and water birds, and to determine the relationships between morphological characteristics and foraging behaviour of waders shorebirds and water birds. The study was conducted in the mudflat area of Jeram and Remis Beaches (in Selangor, Malaysia) from August 2013 to July 2014 using direct observation technique (aided with binoculars and video recorder). Three plots were set-up in Jeram Beach consisted a total of 27 ha meanwhile two plots were set-up in Remis Beach which cover a total area of 28 ha. For abundance study, the birds were counted in four interval periods (i.e. from 0800-1000 hours, 1000- 1200 hours, 1400-1600 hours and 1600-1800 hours) in all tidal states. For foraging behaviour study, the actively foraging birds were watched and their foraging activities were recorded for at least 30 seconds up to a maximum of five minutes. A total of 19,041 individuals of waders were recorded during sampling period. No significant differences were found in bird’s abundance between Jeram and Remis Beaches (t = 2.96, p = 0.05). Although no difference exist between the sampling sites, a significant difference were detected between the sampling plots in Jeram Beach (S = 16.67, p < 0.001) and also between the sampling plots in Remis Beach (W = 78, p = 0.003). Two samples t-test shows a significant difference in avian abundance between migratory and non-migratory seasons (t = 2.39, p = 0.036). A Spearman Rank Correlation highlighted a significant relationship between bill size and foraging time (R = 0.443, p <0.05), bill size and prey size (R = -0.052, p < 0.05), bill size and probing depth (R = 0.42, p = 0.003), and leg-length and water/mud depth (R = 0.706, p < 0.005). A Mann-Whitney U test showed a significant difference in avian abundance between high and low tides (W = 78.0, p < 0.005). A Friedman’s Two-Way ANOVA by rank test proves the significant differences that occurred in bird’s distribution between ebbing, low tide peak and rising tide (S = 17.17, p < 0.0001). χ2 test was used for all behaviours engaged by birds during low tide, and the results show a significant difference between behaviours (χ2 = 1831.9, p < 0.0001). An ANOVA analysis showed no significant difference in the abundance of birds between interval periods (S = 487.0, p = 0.554). Spearman’s rank correlation shows significant relationships between the abundance of bird with the abundance of humans, dogs and vehicles (p < 0.05) in both Jeram and Remis Beaches. Therefore, this study suggests that Jeram and Remis Beaches is important area for waders. Tide and disturbance affect the abundance and behaviours of birds meanwhile time of the day do not affect their abundance and behaviour. The morphological characteristics of bird also influence birds’ foraging behavior.